Aftercare for Survivors of Human Trafficking: A Case Study on Optimal Approach to Recovery and Integration - Abayle, Cherrelyn L.; Candilas, Kurt (Future Science / FSH-PH Publications, 2024)
Human trafficking is a modern-day slavery that mostly disproportionate women in the society. This study aimed to fill the knowledge gaps regarding the aftercare experiences of human trafficking survivors as they navigated their recovery and reintegration into society, with a specific focus on the Philippines. The research investigated the effectiveness of aftercare interventions provided by agency, highlighting the importance of comprehensive and customized support systems. It drew on Empowerment Theory and Ecological Systems Theory to inform its analysis. The study utilized a qualitative intrinsic case study design, employing purposeful sampling to gather insights from social worker, psychologist, house parents, survivors and other professional involved in aftercare. Collecting data using typically involved conducting in-depth interviews, engaging with key informants, and facilitating focus group discussions. Emerging themes were analyzed using Braun and Clarke’s method of thematic analysis. The study uncovered two main themes: